A Model of Readiness of the Future Teacher to Developing the Intellectual-Creative Potential of Junior Schoolchildren - Tаtyаnа Olеgovnа Bondаrеvа; Natalya Nikolaevna Khan; Elena Nikolaevna Pristupa; Asemgul Aleksandrovna Moldazhanova (International Review of Management and Marketing, 2016)
The article considers the problems of preparing the future teacher to developing the intellectual-creative potential of junior schoolchildren. In connection with this, a model is developed of readiness of the future teacher to developing the intellectual-creative potential of junior schoolchildren. The approaches are described that are put into foundation of this model. The psychological-pedagogical conditions in the system of pedagogical education are determined which foster the process of development of the intellectual-creative potential of junior schoolchildren.